1994
DOI: 10.1007/bf01881437
|View full text |Cite
|
Sign up to set email alerts
|

A new concept of photogeneration of cations: Evidence for photoejection of Ca2+ and Li+ from complexes with a crown-ether-linked merocyanine by picosecond spectroscopy

Abstract: Time-resolved transient absorption and gain spectra of DCM-crown and its complexes with Li(+) and Ca(2+) in acetonitrile are measured in the wavelength range 370-670 nm after subpicosecond excitation at 425 nm. The results give evidence for the fast formation of free DCM-crown from both excited complexes, with a faster rate for the Li(+) complex. A two-step mechanism is found for the initial decay (within 30 ps) of the free DCM-crown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It is interesting that the cation which was initially attracted to the receptor is no longer welcome due to the new photogenerated repulsion. These principles were first crystallized to rationalize the increased acidity of phenols in the excited state , and later exploited in the pH jump method for photogenerating proton (or hydroxide) pulses. 175a,, However the generality of these principles and their application to metal ion-sensing phenomena was not realized until Valeur and Lapouyade and Rettig 181-184a had conducted extensive steady state and kinetic studies on 18 and 19 , respectively. Alfimov's systems also display photocontrolled cation binding, although most of them are weakly fluorescent (see 37 233 for an example).…”
Section: Charge-transfer (Ct) Excited States and Relativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that the cation which was initially attracted to the receptor is no longer welcome due to the new photogenerated repulsion. These principles were first crystallized to rationalize the increased acidity of phenols in the excited state , and later exploited in the pH jump method for photogenerating proton (or hydroxide) pulses. 175a,, However the generality of these principles and their application to metal ion-sensing phenomena was not realized until Valeur and Lapouyade and Rettig 181-184a had conducted extensive steady state and kinetic studies on 18 and 19 , respectively. Alfimov's systems also display photocontrolled cation binding, although most of them are weakly fluorescent (see 37 233 for an example).…”
Section: Charge-transfer (Ct) Excited States and Relativesmentioning
confidence: 99%
“…[210][211][212][213][214] A related study is available for 2,2′bipyridyl-3,3′-diol when it binds Zn(II). 215 For instance, the weakened cation binding in the excited state (which leads to cation disengagement) [178][179][180][181][182][183][184] can be quantitated in this way. [211][212][213] Prior to this benevolent invasion of biology by molecular fluorescent sensors/switches, there were examples quietly serving analytical chemistry.…”
Section: Signaling Recognition Eventsmentioning
confidence: 99%
“…Irreversible photoinduced changes in the chemical structure of a calcium chelator (EGTA type) with the effect of supressing the coordinating role of a nitrogen atom was shown to result in a decrease of the stability constant of the complex by a factor of 10−30 . In previous papers, , we provided evidence for cation photorelease from Li + − and Ca 2+ −DCM−crown complexes by picosecond pump−probe spectroscopy and suggested that photoejection occurs from the excited complex, once the latter has relaxed to its charge−transfer state reported a picosecond study of a crown−phenylstilbene derivative complexed with Ca 2+ and proposed an excited-state mechanism including a reversible breaking of the nitrogen−calcium interaction followed by the reversible formation of a solvent-separated cation−probe pair.…”
Section: Introductionmentioning
confidence: 92%
“…Further, the ligand hole contribution at the wavelength of the isosbestic point, 485 nm, if any, is strongly overshadowed by the LMCT GSB and the ESA of S n (d) origin. We note that analyzing isosbestic points in transient absorption spectra at the many picoseconds timescale has precedence. …”
Section: Results: Transient Optical Spectroscopy and Td-dft Calculationsmentioning
confidence: 99%